Culture Shock dan Negosiasi Nilai Mahasiswa Non-Pesantren dalam Budaya Akademik Perguruan Tinggi Berbasis Pesantren - Siti Nur Kasanah; Sabarudin Sabarudin; Adi Kusmanto (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study aims to analyze the culture shock experiences of non-pesantren students in the academic culture of a pesantren-based higher education institution. The study employs a qualitative approach using a case study design, involving in-depth interviews with students from a general education background at IAI Al-Muhammad Cepu. Data analysis was conducted thematically through open coding, theme categorization, and interpretation based on Oberg’s theory of culture shock. The results indicate that students experience culture shock through the stages of honeymoon, frustration, adjustment, and adaptation. The frustration phase is the most dominant stage due to the hidden curriculum, differences in communication patterns and language use, as well as academic assumptions rooted in pesantren experiences that non-pesantren students cannot fully access. This study found that the students’ adaptation process did not take the form of full assimilation but rather through partial and ongoing value negotiation. Students actively select, adjust, and retain parts of their original identities during the process of adapting to the pesantren academic culture. These findings expand the study of culture shock within the context of pesantren-based higher education and demonstrate that students’ cultural adaptation occurs dynamically through a process of value selection and adjustment.